Analisis Brand Awareness Terhadap Keputusan Pembelian Produk Minuman Teh Botol Sosro Pada Mahasiswa Universitas Bina Sarana Informatika Kampus Pemuda 2022 - Purwaningrum, Chanissa (Rifa'Institute, 2022)
One of the variables that affect the product mix is ??the brand. Building a brand in a product requires a strong effort to create a real or symbolic product difference. A strong product will get a high Top of Mind level. If this happens, it can be concluded that the product brand already exists in the minds of consumers. Building a good brand can be done through the promotion mix. In the promotional mix the variables that influence are: sales promotion, advertising, sales force, public relations, direct marketing. In general, the purpose of this study is to get an overview of the brand equity of Teh Botol. As for more details, the purpose of this study is to analyze the perception of Brand Awareness on the Purchase Decision of Sosro Botol Teh Beverage Products. The research was conducted on the people of Jakarta on social media Instagram, using questionnaires and literature techniques. The results of the calculation of Brand Recognition Brand Awareness for 47 respondents are as follows: 44 respondents (93.6%) stated that they knew the Teh Botol Sosro brand and included it in their answers, 3 respondents (6.4%).